The Everglades handbook understanding the ecosystem - Lodge, Thomas E. 1943-; Davis, Stephen E. III (CRC Press, 2024)
The Everglades Handbook: Understanding the Ecosystem, Fifth Edition is packed with scientific information about the greater Everglades ecosystem, taking into account how drastically the Everglades has changed. The book covers disciplines ranging from ecology, geology, climatology, hydrology, simplified biogeochemistry, and anthropology to conservation biology. The fifth edition of this bestselling guide presents expanded treatment of subjects where our knowledge of the Everglades and its restoration has greatly improved as well as updates throughout. This more detailed coverage includes a new chapter ‘Everglades Chemistry – A Primer’ and an expanded section on the role of human intervention in Everglades restoration, as well as numerous new graphics that bring the science to life. Written in Tom Lodge’s trademark accessible style combined with the expertise of new co-author Stephen E Davis III, Chief Science Officer with the Everglades Foundation, this extensively researched text is essential reading for anybody trying to understand the challenges we face in restoring this unique ecosystem.